Inhaled nicotine replacement therapy - David Cipolla; Igor Gonda (Elsevier, 2015)
There are a large number of smokers who want to quit smoking but have failed in their attempts to do so, with many having been unsuccessful at quitting multiple times over their lifetime. The existing marketed nicotine replacement therapies (NRT) have only marginal effectiveness and none provide a comparable physiological response to that derived from cigarette smoking; that is, rapid absorption of nicotine from the lung leading to peak levels of nicotine in the bloodstream to target the receptors in the brain. Instead, existing NRTs produce a slower and delayed rise in nicotine blood levels which is less effective at reducing the craving sensations. Published data for electronic cigarettes show that they typically deliver nicotine with a profile closer to that for nicotine patches, with a slow rise that can take 30-60 min, or longer, to reach the same peak nicotine concentration that is produced in less than 3 min from a single cigarette. A number of attempts have been made to develop an inhaled product which would deliver the nicotine through the lung and mimic the physiological response from smoking, but many of them produced intolerable aversive reactions or delivered an ineffective dose. This paper discusses examples of the potential for the recent inhaled nicotine products in development to be effective as NRTs, but is not meant to be a comprehensive review.